Gibson's fabulous flat-top guitars : an illustrated history & guide - Whitford, Eldon (GPI Books, 1994)
It's for good reason that Gibson is the most recognized name in the history of the guitar. From the 1920s to the present, Gibson and its flat-top guitars have become a slice of Americana. Whether the musicians you listen to have been from the South or from the North, urban or rural, white or African-American, old or young, it's likely that a Gibson was involved in creating the music. To artists as diverse as Bob Dylan, John Hiatt, Lightnin' Hopkins, Ian & Sylvia, the Everly Brothers, Alan Jackson, and Mance Lipscomb, Gibson makes the guitar that makes the music, in a variety of genres ranging from folk and blues and jazz to country and pop and rock. Through more than two hundred photos and detailed text, this book chronicles the development and evolution of Gibson's fabulous flat-tops, showing why these guitars have been the instruments of choice to so many great musicians, professional and amateur alike, over the last seventy years. Gibson's Fabulous Flat-Top Guitars explains why some many guitar players over the decades have felt that only a Gibson is good enough.